STUDENTS’ PERCEPTION TOWARDS THE USAGE OF ARTIFICIAL INTELLIGENCE IN TERTIARY EDUCATION - Mathes, Winifred Thivyamalar A/P; Magantran, Shamni; Abd Rahman, Nik Siti Maisarah Binti (Selangor Humaniora Review, 2023)
This study investigates the perceptions of tertiary education students on using Artificial Intelligence (AI) to enhance academic performance. With AI’s growing presence across various sectors, including education, it is imperative to understand the student perspective on its integration into their learning environment. Utilising a quantitative approach, the research encompasses a cross-sectional survey of one hundred (100) students from diverse colleges and universities across Malaysia. The findings reveal a notable familiarity among students with AI tools and a significant proportion leveraging these technologies for academic improvement. However, the study also uncovers prevalent concerns about privacy risks associated with AI usage. These insights reflect the current trends in AI adoption in educational settings and highlight critical areas of consideration for educators and policy-makers in balancing technological advancement with student privacy and well-being. The implications of these findings are substantial, offering a nuanced understanding of student attitudes towards AI in education and guiding future strategies for its ethical and effective implementation.